Study on Biofortification of Rice by Targeted Genetic Engineering - Hossain, Sumon M; Mohiuddin, AKM (International Journal of Agricultural Research, Innovation and Technology, 2013)
Micronutrient malnutrition is a major health problem in Bangladesh and also in many other developing countries, where a diversified diet is not affordable for the majority. In the present world- one, out of seven people suffers from hunger. Yet, there is a stealthier form of hunger than lack of food: micronutrient malnutrition or hidden hunger. While often providing enough calories, monotonous diets (of rural poor) frequently fail to deliver sufficient quantities of essential minerals and vitamins. Due to micronutrient deficiencies different characteristic features have been observed to the victims. Various estimates indicate that over two-thirds of the world population, for the most part women and children specially, pre-school children are deficient in at least one micronutrient. This can have devastating consequences for the life, health and well being of the individuals concerned (like premature death, blindness, weakened immune systems etc). Genetic engineering approach is the upcoming strategy to solve this problem. Genetically engineered biofortified staple crops specially, rice that are high in essential micronutrients (Fe, Zn, vitamin A) and adapted to local growing environments have the potential to significantly reduce the prevalence of micronutrient deficiencies specially to the rural poor. DOI: http://dx.doi.org/10.3329/ijarit.v2i2.14011 Int. J. Agril. Res. Innov. & Tech. 2 (2): 25-35, December, 2012